Efforts to Resolve the Misuse of Customer Funds at The Village Credit Institution (VCI) of Sibang Kaja Customary Village - Ida Ayu Sadnyini; Ni Wayan Pariasih Cahyana (Fakultas Hukum, Universitas Warmadewa, 2022)
Village Credit Institution (VCI) of customary village/desa pekraman in Bali is a village-owned financial business entity that carries out business activities in the village and for krama desa. In this case, the authors conducted research on the VCI of Sibang Kaja Customary Village, Abiansemal District, Badung Regency, Bali Province. This research was conducted to determine and examine (1) the factors that cause customer funds cannot be disbursed at the VCI of Sibang Kaja Customary Village; (2) the efforts to resolve the misuse of customer funds at the VCI of Sibang Kaja Customary Village. This is empirical and juridical research, using the qualitative descriptive method and Aristotle’s theory of justice. This research used primary and secondary data. Data were obtained through in-depth interviews. Three factors that cause customer funds cannot be disbursed: (a) the VCI does not record the money deposited by customers in their passbooks; (b) customers deposit their money through VCI employees in charge of collecting money in the field, yet, the money is not deposited to the VCI, resulting in the customer suffering a loss; (c) non-fulfillment of customer rights. The effort to resolve the misuse of customer funds at the VCI of Sibang Kaja Customary Village is through deliberation/paruman of the customary village. The result of deliberation/paruman of the customary village is reconciliation between the customers of the VCI and the perpetrators. Sanctions given on the perpetrators are: managers and employees of the VCI who, in carrying out their duties, violate the provisions and cause harm to the VCI must: (a) provide compensation according to the losses incurred; (b) receive customary sanctions according to awig-awig and perarem; (c) receive sanctions according to the applicable law.